Long‐Term Outcomes of Spinal Cord Stimulation With Percutaneously Introduced Paddle Leads in the Treatment of Failed Back Surgery Syndrome and Lumboischialgia. Issue 6 (7th January 2013) - Logé, David; Vanneste, Sven; Vancamp, Tim; Rijckaert, Dirk
<x xml:space="preserve">Abstract</x> Objective The study aims to evaluate the long‐term clinical and technical efficacy of recently developed percutaneously introducible plate electrodes for spinal cord stimulation. Methods Twenty‐one patients diagnosed with failed back surgery syndrome (FBSS) or lumboischialgia were implanted with a small profile plate‐type electrode. Patients were followed‐up long term and were asked at baseline, after trial, and during each follow‐up visit to score their pain on a visual analog scale (VAS) for pain now, worst pain last week, least pain last week, and mean pain last week. Pain location, electrophysiologic parameters, and number of reprogrammings were collected as well. Furthermore, each patient was asked if he/she would redo the procedure post trial and at each of the follow‐up visits. Results A total of 21 patients were prospectively followed up long term. With a mean follow‐up of 40.8 months, a significant mean reduction in patient self‐reported pain from baseline to postoperative of 75.79% pain reduction was seen at follow‐up 1 and 62.52% at follow‐up 2. A significant decrease was obtained for, respectively, pain at the present moment, VAS pain worst last week, VAS pain least last week, and VAS pain mean last week in comparison with baseline VAS scores. All patients indicated that they would redo the procedure. Conclusion Percutaneous implantation of small profile paddle leads in patients with FBSS and lumboischialgia produces favorable results over the long term that are at least comparable with surgical implanted paddle leads. The percutaneous approach also allows nonsurgically trained pain physicians to introduce paddle leads. Indices like if patients would redo the procedure may be more appropriate for analyzing long‐term outcomes than the arbitrarily taking 50% reduction in VAS scores.